DC microgrids: review and applications - Blasi, Bronson Richard (Kansas State University, 2013)
This paper discusses a brief history of electricity, specifically alternating current (AC) and direct current (DC), and how the current standard of AC distribution has been reached. DC power was first produced in 1800, but the shift to AC occurred in the 1880’s with the advent of the transformer. Because the decisions for distribution were made over 100 years ago, it could be time to rethink the standards of power distribution. Compared to traditional AC distribution, DC microgrids are significantly more energy efficient when implemented with distributed generation. Distributed generation, or on-site generation from photovoltaic panels, wind turbines, fuel cells, or microturbines, is more efficient when the power is transmitted by DC. DC generation, paired with the growing DC load profile, increases energy savings by utilizing DC architecture and eliminating wasteful conversions. Energy savings would result from a lower grid strain and more efficient utilization of the utility grid. DC distribution results in a more reliable electrical service due to short transmission distances, high service reliability when paired with on-site generation, and efficient storage. Occupant safety is a perceived concern with DC microgrids due to the lack of knowledge and familiarity in regards to these systems. However, with proper regulation and design standards, building occupants never encounter voltage higher than 24VDC, which is significantly safer than existing 120VAC in the United States. DC Microgrids have several disadvantages such as higher initial cost due, in part, to unfamiliarity of the system as well as a general lack of code recognition and efficiency metric recognition leading to difficult certification and code compliance. Case studies are cited in this paper to demonstrate energy reduction possibilities due to the lack of modeling ability in current energy analysis programs and demonstrated energy savings of approximately 20%. It was concluded that continued advancement in code development will come from pressure to increase energy efficiency. This pressure, paired with the standardization of a 24VDC plug and socket, will cause substantial increases in DC microgrid usage in the next 10 years.
Keywords: DC microgrid; Direct current microgrid; DC building distribution; Conversion losses; Direct current building distribution; DC power distribution; Architectural engineering (0462); Electrical Engineering (0544); Sustainability (0640)